Detection of improvement in the treatment for skin cancer using image processing techniques - Senthil Ragava, Valayapalayam Kittusamy; Venkatesh, Chakrapani (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This paper presents an innovative idea for identifying the improvement in the treatment for skin cancer from the sequence of photographs of cancer affected area for the patient’s who are having sodium bicarbonate as medicine as suggested by the Doctor. The proposed scheme uses two methods for classification of skin cancer. These methods are compared for their effectiveness. The improvement in the treatment was also tested and proved.